Malaria burden and control in Bangladesh and prospects for elimination: an epidemiological and economic assessment - Dr. Ubydul Haque, PhD; Hans J Overgaard, PhD; Archie C A Clements, PhD; Douglas E Norris, PhD; Nazrul Islam, MPh; Jahirul Karim, MPh; Shyamal Roy, MSc; Waziul Haque, MSc; Moktadir Kabir, MPh; David L Smith, PhD; Gregory E Glass, PhD (Elsevier, 2014)
Background: Malaria is endemic in 13 of 64 districts in Bangladesh. About 14 million people are at risk. Some evidence suggests that the prevalence of malaria in Bangladesh has decreased since the the Global Fund to Fight AIDS, Tuberculosis and Malaria started to support the National Malaria Control Program (NMCP) in 2007. We did an epidemiological and economic assessment of malaria control in Bangladesh. Methods: We obtained annually reported, district-level aggregated malaria case data and information about disbursed funds from the NMCP. We used a Poisson regression model to examine the associations between total malaria, severe malaria, malaria-attributable mortality, and insecticide-treated net coverage. We identified and mapped malaria hotspots using the Getis-Ord Gi* statistic. We estimated the cost-effectiveness of the NMCP by estimating the cost per confirmed case, cost per treated case, and cost per person of insecticide-treated net coverage. Findings: During the study period (from Jan 1, 2008, to Dec 31, 2012) there were 285 731 confirmed malaria cases. Malaria decreased from 6·2 cases per 1000 population in 2008, to 2·1 cases per 1000 population in 2012. Prevalence of all malaria decreased by 65% (95% CI 65-66), severe malaria decreased by 79% (78-80), and malaria-associated mortality decreased by 91% (83-95). By 2012, there was one insecticide-treated net for every 2·6 individuals (SD 0·20). Districts with more than 0·5 insecticide-treated nets per person had a decrease in prevalence of 21% (95% CI 19-23) for all malaria, 25% (17-32) for severe malaria, and 76% (35-91) for malaria-associated mortality among all age groups. Malaria hotspots remained in the highly endemic districts in the Chittagong Hill Tracts. The cost per diagnosed case was US$0·39 (SD 0·02) and per treated case was $0·51 (0·27); $0·05 (0·04) was invested per person per year for health education and $0·68 (0·30) was spent per person per year for insecticide-treated net coverage. Interpretation: Malaria elimination is an achievable prospect in Bangladesh and failure to push for elimination nearly ensures a resurgence of disease. Consistent financing is needed to avoid resurgence and maintain elimination goals. Funding: None.